ANALISIS BUKU TEKS “AKU CINTA BAHASA ARAB 4” KELAS IV KURIKULUM 2013 MADRASAH IBTIDAIYAH KARYA AGUS WAHYUDI (TINJAUAN SEGI KELAYAKAN ISI) - Muhammad Nur Asmawi; Ulfa Djahadi (Albariq: Jurnal Pendidikan Bahasa Arab, 2021)
This research is a library research. In collecting research data, the researcher uses documentation techniques. And in analyzing the data, the researcher uses content analysis, where this analysis is used to understand the content and meaning of various studies. Sources of data used are primary data and secondary data. The results of this study indicate that the textbook "I Love Arabic 4" grade IV curriculum 2013 Madrasah Ibtidaiyah by Agus Wahyudi has met the eligibility requirements set by BSNP and is considered suitable for use with a percentage of eligibility of 88% or in the very good category. The implication of this research is as a material for improving the quality of books for writers/publishers, and can be used as a supporting book to add insight and understanding of the material.